2013
DOI: 10.1108/17538391311310752
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing service quality factors in Iranian Islamic banking using a fuzzy approach

Abstract: Purpose -The aim of the present research is firstly to examine and recognize the quality elements of services in the banks by SERVQUAL instrument and some Islamic banking factors. Secondly, the aim is to prioritize these factors based on fuzzy TOPSIS. Fuzzy logic provides a useful tool for dealing with decisions in which the phenomena are vague. Design/methodology/approach -The present research was performed among bank customers. The required information was gathered through a designed questionnaire. Using fuz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
(39 reference statements)
1
12
0
Order By: Relevance
“… true normalSQI true¯ of 3.28 showed that occupiers of shopping complexes in the study area rated the services of property managers under empathy dimension to be “fair.” This could be that property managers in the study area lack customer relations. This finding confirmed the work of Amirzadeh and Reza Shoorvarzy (2013) and proved that the empathy dimension of banking SQ was low quality.…”
Section: Presentation and Discussion Of Resultssupporting
confidence: 89%
See 2 more Smart Citations
“… true normalSQI true¯ of 3.28 showed that occupiers of shopping complexes in the study area rated the services of property managers under empathy dimension to be “fair.” This could be that property managers in the study area lack customer relations. This finding confirmed the work of Amirzadeh and Reza Shoorvarzy (2013) and proved that the empathy dimension of banking SQ was low quality.…”
Section: Presentation and Discussion Of Resultssupporting
confidence: 89%
“…The SERVPERF model measured SQ solely based on performance to suggest that performance-based measure explains the variance in the overall measure of SQ better, and this assertion has been supported by scholars such as Boulding et al (1993) and Gupta and Singh (2017) that the SERVPERF model indicated superiority in terms of its reliability, convergent and discriminant validity. Researchers have used both SERVQUAL and PERVSERV models to identify and measure SQ in varied service sectors, such as real estate agency (Araloyin and Ojo, 2011), facility management (Ikediashi et al , 2015), shopping center management (Harmse, 2014), quantity surveying services (Procter and Rwelamila, 1999; Akinsiku, 2014), transportation service (Aydin, 2017; Deb and Ahmed, 2018), banking services (Fragoso and Espinoza, 2017; Amirzadeh and Reza Shoorvarzy, 2013) and restaurant service (Namin, 2017), among others.…”
Section: Service Quality Dimensions and Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, an important way to make a strong competitive position would be consumer needs accurately and completely understanding. Today, no organization would be successful except it attract and retain enough consumers (Amirzadeh and Shoorvarzy, 2013). Therefore, this study is beneficial for practitioners by offering insight into choice criteria for ICC.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…Despite the fact that much effort is being invested by researchers along with academicians toward understanding the concept service quality regarding Islamic banking, however, less is known about service quality and customer satisfaction as well as loyalty regarding Islamic banking compared to its conventional counterpart. Moreover, researchers have also claimed that the application of SERVQUAL is at an initial stage in the Islamic banking sector (Amirzadeh and Shoorvarzy, 2013). This calls for further investigation of service quality in the context of Islamic banking.…”
Section: Introductionmentioning
confidence: 99%